Formation of the system of ensuring financial security of entrepreneurs on the basis of controlling Формирование системы обеспечения финансовой безопасности субъектов предпринимательства на основе контроллинга - Kuzenko Tatyana B.; Poltinina Olga P. (Problemi Ekonomiki, 2013)
The article substantiates expediency of introduction of controlling into the system of ensuring financial security of entrepreneurs. It identifies components of the system of ensuring financial security of entrepreneurs on the basis of controlling, namely: goals, tasks, functions, prerequisites of introduction, methods and subjects of ensuring financial security of entrepreneurs. It develops a methodical approach to identification of the use of tactical and strategic controlling in ensuring financial security of entrepreneurs, which allows performance of objective diagnostics of the level of financial security and identification of main threats to financial interests of entrepreneurs. It offers a structural and functional model of ensuring financial security of entrepreneurs on the basis of controlling, which generalises approaches to construction of the system of ensuring financial security of entrepreneurs on the basis of controlling and identifies stages of its construction. В статье обоснована целесообразность внедрения контроллинга в систему обеспечения финансовой безопасности субъектов предпринимательства. Определены составляющие элементы системы обеспечения финансовой безопасности субъектов предпринимательства на основе контроллинга, а именно: определены цели, задачи, функции, предпосылки внедрения, методы и субъекты обеспечения финансовой безопасности субъектов предпринимательства на основе контроллинга. Разработан методический подход к определению использования тактического и стратегического контроллинга в обеспечении финансовой безопасности субъектов предпринимательства, который позволяет осуществлять объективную диагностику уровня финансовой безопасности и определять основные угрозы финансовым интересам владельцев субъектов предпринимательства. Предложена структурно-функциональная модель обеспечения финансовой безопасности субъектов предпринимательства на основе контроллинга, которая обобщает подходы к построению системы обеспечения финансовой безопасности субъектов предпринимательства на основе контроллинга и определяет этапы ее построения.